A consensus statement for trauma surgery capacity building in Latin America (2021)
Background Trauma is a significant public health problem in Latin America (LA), contributing to substantial death and disability in the region. Several LA countries have implemented trauma registries and injury surveillance systems. However, the region lacks an integrated trauma system. The consensus conference’s goal was to integrate existing LA trauma data collection efforts into a regional trauma program and encourage the use of the data to inform health policy. Methods We created a consensus group of 25 experts in trauma and emergency care with previous data collection and injury surveillance experience in the LA. region. Experts participated in a consensus conference to discuss the state of trauma data collection in LA. We utilized the Delphi method to build consensus around strategic steps for trauma data management in the region. Consensus was defined as the agreement of ≥ 70% among the expert panel. Results The consensus conference determined that action was necessary from academic bodies, scientific societies, and ministries of health to encourage a culture of collection and use of health data in trauma. The panel developed a set of recommendations for these groups to encourage the development and use of robust trauma information systems in LA. Consensus was achieved in one Delphi round. Conclusions The expert group successfully reached a consensus on recommendations to key stakeholders in trauma information systems in LA. These recommendations may be used to encourage capacity building in trauma research and trauma health policy in the region.